Advantages and Disadvantages of Renewable Energy Sources Utilization - Maradin, Dario (International Journal of Energy Economics and Policy, 2021)
Renewable energy sources are still not the predominant energy resource in the energy sector, although in certain developed countries they participate in a significant share in electricity generation. It is estimated that world energy consumption from renewable energy sources exceeds 20% at the present and continues to grow. Renewable energy sources appear as an additional source of energy in the conventional electro-industry. The main reason for the increasing investment and exploitation of renewables is certainly environment preservation and environmental aspect of sustainability. This study seeks to expand the existing literature and contribute to a comprehensive understanding of the characteristics of renewable energy sources as a whole. Therefore, the purpose of this paper is to determine the advantages and disadvantages of renewable energy sources utilization in general, without considering the individual type of renewables, such as wind or solar energy. Thereby, the paper presents numerous advantages of using renewable energy in the electricity generation, such as environment preservation in terms of reduced greenhouse gas emissions or improvement of innovations and technical/technological development. There are also presented certain disadvantages of renewables in the production of electricity, such as dependence on weather conditions or low energy efficiency and low ability to produce electricity. Keywords: Renewable energy sources, boosting the economy, environment preservation, renewables limitations JEL Classifications: Q42; Q56 DOI: https://doi.org/10.32479/ijeep.11027